2019
DOI: 10.3389/fimmu.2019.02152
|View full text |Cite
|
Sign up to set email alerts
|

Host Components Contributing to Respiratory Syncytial Virus Pathogenesis

Abstract: Respiratory syncytial virus (RSV) is the most prevalent viral etiological agent of acute respiratory tract infection. Although RSV affects people of all ages, the disease is more severe in infants and causes significant morbidity and hospitalization in young children and in the elderly. Host factors, including an immature immune system in infants, low lymphocyte levels in patients under 5 years old, and low levels of RSV-specific neutralizing antibodies in the blood of adults over 65 years of age, can explain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
58
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(60 citation statements)
references
References 266 publications
(313 reference statements)
1
58
0
1
Order By: Relevance
“…The disease caused by hRSV is characterized mainly by the infiltration of eosinophils and neutrophils into the airways. An increase infiltration of neutrophils can contribute to lung damage ( 210 212 ). Even though CD8 + T cells are key in the clearance of the virus, it has been reported that the depletion of the CD4 + and CD8 + T cells in mice decreased the severity of the illness ( 213 215 ).…”
Section: Antiviral Activity Of Dcs Against Rna Virusesmentioning
confidence: 99%
“…The disease caused by hRSV is characterized mainly by the infiltration of eosinophils and neutrophils into the airways. An increase infiltration of neutrophils can contribute to lung damage ( 210 212 ). Even though CD8 + T cells are key in the clearance of the virus, it has been reported that the depletion of the CD4 + and CD8 + T cells in mice decreased the severity of the illness ( 213 215 ).…”
Section: Antiviral Activity Of Dcs Against Rna Virusesmentioning
confidence: 99%
“…The G, F, and SH proteins are envelope proteins. The P, N, M, M2, and L proteins are present just below the envelope [4,5]. The virus binds to the host cell surface using F-protein which later directs its entry into the cell leading towards syncytia formation [6].…”
Section: Introductionmentioning
confidence: 99%
“…Regardless of the studied tissue, HRSV is consensually described as a major disruptor of the host immune response [47][48][49]. Here, comparing our signatures with 3 other ones extracted from pediatric whole blood transcriptomic analyses [28][29][30], we highlighted the common deregulation of 7 genes, independently of the tissue, and interestingly, 242 genes that seem to be specific to nasal epithelium HRSV-induced gene expression.…”
Section: Discussionmentioning
confidence: 78%